(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract. The system of agricultural advisory services is an effective tool for improving agricultural culture, increasing the yield of agricultural crops, the productivity of farm animals and, ultimately, the efficiency of economic activity in the agricultural sphere. This happened first in all those states in which the agricultural sector was on the path to industrialization. The market began to dictate its conditions, because self-isolation and closed-mindedness ultimately lead to stagnation and degradation. The integration of Ukrainian agriculture into the European economic system requires bringing the agricultural sector to a higher level and requires a certain training of domestic agricultural producers for the adaptation of the implemented policy in the EU - a deep understanding of the content and essence of all components of the common agrarian policy.